Evaluating the effectiveness of health communication: a proposed tool for evaluating sexually transmitted infections (STI) prevention campaigns (abstract: p. 16) - Rothberg, Danilo [UNESP]; Ferreira, Vinícius Lauriano; Muniz, Aressa Joel [UNESP]; Mendonça, Ana Valéria Machado (FapUNIFESP (SciELO), 2022)
What constitutes effective communication for health promotion and the prevention of STI among young people? This article proposes a methodology for evaluating the effectiveness of public publicity campaign pieces, such as videos, posters, leaflets, audio and print media, and social media posts. The indicators used to determine effectiveness were taken from the specialist literature and systematized in the form of an evaluation guide consisting of seven thematic blocks structured around normative propositions. This article describes the guide, the rationale behind it, and its application as a health communication tool for determining effectiveness in theory and practice. The guide provides an objective tool that can be applied by individual researchers or teams to a broad range of corpora.
Calidad de la comunicación promotora de la salud: ¿cómo evaluarla? Propuesta de instrumento de evaluación de campañas de prevención de infecciones de transmision sexual (ITSs) (resumen: p. 16)
Qualidade da comunicação promotora da saúde: como avaliar? Proposta de instrumento de avaliação de campanhas de prevenção de infecções sexualmente transmissíveis (ISTs)
Keywords: Health communication; Public health campaigns; STI prevention